Islamic Republic of Afghanistan : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the First Review Under the Poverty Reduction and Growth Facility (PRGF) for Afghanistan. Despite a difficult security environment and persistent expenditure pressures, Afghanistan's performance during the first six months of 2006/07 was in line with the program. The authorities met all the end-September 2006 quantitative performance criteria and indicative targets, the structural performance criterion, and most structural benchmarks, except those related to state-owned banks. The overall fiscal strategy for the remainder of 2006/07 and for 2007/08 strikes a balance between addressing critical spending pressures and fiscal sustainability.